Answer:
5.25 miles
Step-by-step explanation:
15 min=1/4 of hour
12/4=3
9/4=2.25
3+2.25=5.25
12 x 6s - 8 x 4s = 72s - 32s = 40s
Answer:
there is no answer
Step-by-step explanation:
Explanation:
Since we have given that
![(2x+1)^2-2(2x+1)](https://tex.z-dn.net/?f=%282x%2B1%29%5E2-2%282x%2B1%29)
Now, we have to prove it as
![(2x+1)(2x-1)](https://tex.z-dn.net/?f=%282x%2B1%29%282x-1%29)
Now, start the iterations:
![(2x+1)^2-2(2x+1)\\\\=4x^2+1+4x-4x-2\\\\=4x^2+1-2\\\\=4x^2-1\\\\=(2x)^2-1\\\\=(2x+1)(2x-1)](https://tex.z-dn.net/?f=%282x%2B1%29%5E2-2%282x%2B1%29%5C%5C%5C%5C%3D4x%5E2%2B1%2B4x-4x-2%5C%5C%5C%5C%3D4x%5E2%2B1-2%5C%5C%5C%5C%3D4x%5E2-1%5C%5C%5C%5C%3D%282x%29%5E2-1%5C%5C%5C%5C%3D%282x%2B1%29%282x-1%29)
So, first blank will be filled with
![4x^2+4x+1](https://tex.z-dn.net/?f=4x%5E2%2B4x%2B1)
Second blank will be filled with
![4x^2-1](https://tex.z-dn.net/?f=4x%5E2-1)
Hence proved.
43 i alredy learned that in school